Seismic Imaging of a Shale Landscape Under Compression Shows Limited Influence of Topography‐Induced Fracturing. Issue 17 (27th August 2021) - Ma, Lisa; Oakley, David; Nyblade, Andrew; Moon, Seulgi; Accardo, Natalie; Wang, Wei; Gu, Xin; Brubaker, Kristen; Mount, Gregory J.; Forsythe, Brandon; Carr, Bradley J.; Brantley, Susan L.
Abstract: We used seismic refraction to image the P‐wave velocity structure of a shale watershed experiencing regional compression in the Valley and Ridge Province (USA). From estimates showing strong compressional stress, we expected the depth to unweathered bedrock to mirror the hill‐valley‐hill topography ("bowtie pattern") by analogy to seismic velocity patterns in crystalline bedrock in the North American Piedmont that also experience compression. Previous researchers used failure potentials calculated for strong compression in the Piedmont to suggest fractures are open deeper under hills than valleys to explain the "bowtie" pattern. Seismic images of the shale watershed, however, show little evidence of such a "bowtie." Instead, they are consistent with weak (not strong) compression. This contradiction could be explained by the greater importance of infiltration‐driven weathering than fracturing in determining seismic velocities in shale compared to crystalline bedrock, or to local perturbations of the regional stress field due to lithology or structures. Plain Language Summary: Rock mechanic theory suggests that the depth to crystalline bedrock under hill‐valley‐hill landscapes mirrors the land surface when the landscape experiences strong compression. We tested for this in a region of compression for a watershed on shale and found the depth pattern was consistent only with weak compression. This observation may be because infiltration and chemical weathering are more important than mechanical fracturing in controlling density of near‐surface shale. Alternatively, local effects related to the last glacial advance or the differences in rock types might explain the observation. The depth of weathering (depth to bedrock) is apparently not only controlled by fracturing but rather is heavily influenced by hydrogeochemical processes on shale. Key Points: The P‐wave velocity structure of a shale watershed under compression is imaged Seismic images show little evidence of the expected bowtie structure Results are explained by greater importance of chemical weathering than fracturing in determining seismic velocities in shale landscapes